CEO preferences and acquisitions - Dirk Jenter; Katharina Lewellen (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper explores the impact of target CEOs' retirement preferences on the incidence, the pricing, and the outcomes of takeover bids. Mergers frequently force target CEOs to retire early, and CEOs' private merger costs are the forgone benefits of staying employed until the planned retirement date. Using retirement age as an instrument for CEOs' private merger costs, we find strong evidence that target CEO preferences affect merger patterns. The likelihood of receiving a takeover bid increases sharply when target CEOs reach age 65. The probability of a bid is close to 4% per year for target CEOs below age 65 but increases to 6% for the retirement-age group, a 50% increase in the odds of receiving a bid. This increase in takeover activity appears discretely at the age-65 threshold, with no gradual increase as CEOs approach retirement age. Moreover, observed takeover premiums and target announcement returns are significantly lower when target CEOs are older than 65, reinforcing the conclusion that retirement-age CEOs are more willing to accept takeover offers. These results suggest that the preferences of target CEOs have first-order effects on both bidder and target behavior.
Keywords: G30; G34; 330; mergers & acquisitions; CEO preferences; principal-agent problems; Übernahme; Führungskräfte; Präferenztheorie; Altersgrenze; Prinzipal-Agent-Theorie; USA